Coach-led preventive training program in youth soccer players improves movement technique - Pryor, J. L.; Root, H. J.; Vandermark, L. W.; Pryor, R. R.; Martinez, J. C.; Trojian, T. H.; Denegar, C. R.; DiStefano, L. J. (Journal of Science and Medicine in Sport, 2017)
Abstract: Long-term implementation of preventive training programs (PTP) in youth sport requires coach involvement. However, the optimal training of coaches to effectively implement a PTP remains unknown. It is also unknown if the benefits of PTP can be enhanced with multiple sport seasons of exposure. Objectives: To evaluate the influence of prior PTP exposure on movement technique in youth soccer players after completing a coach-led PTP. Design: Cluster-randomized controlled trial. Methods: Twelve youth soccer teams (n = 89; age range 8-14 years) were divided into groups with (Experience (EXP); 6 teams [n = 18 females, n = 25 males]) and without (Novice (NOV); 6 teams [n = 30 females, n = 16 males]) previous professional-led PTP experience. The coaches and players of the EXP teams were exposed to an eight-week professional-led PTP before the coach-led PTP. EXP and NOV coaches attended the educational workshop prior to implementing the coach-led PTP. The Landing Error Scoring System (LESS) was used to evaluate movement technique. Results: Both groups improved LESS scores over time (mean difference ± SD [post-pre] = -0.8 ± 0.2, 95%CI [-1.2, -0.4], p = 0.0001). Of the 64 participants classified as high risk for injury (LESS =5) prior to PTP implementation, a greater proportion of EXP (n = 14) compared to NOV (n = 7) participants changed risk classification from high to low (LESSdelta >= 1 and LESS <5; p = 0.03). Conclusions: Our PTP enhanced movement technique regardless of PTP experience, but the benefits of the PTP impacted a proportionally greater number of players with previous PTP experience supporting continued PTP implementation. Coaches effectively implemented an exercise-based PTP after attending a training workshop regardless of previous PTP experience.